2014
DOI: 10.1016/j.ccr.2013.09.011
|View full text |Cite
|
Sign up to set email alerts
|

The coordination chemistry and magnetism of some 3d–4f and 4f amino-polyalcohol compounds

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
83
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(86 citation statements)
references
References 70 publications
1
83
0
Order By: Relevance
“…[2][3][4] Therefore, the synthesis and characterization of high-nuclearity 3d-4f SMMs have attracted intensive attention in recent years. [5][6][7][8][9] Although many studies on 4f-4f or 3d-3d interactions have been reported, [10][11][12][13][14][15][16][17] research on 3d-4f exchange interactions is less developed. [18][19][20][21][22][23][24] Furthermore, according to the model of free-ion electron densities for all Ln III ions, the shape of the 4f electron density for the Dy III ion is oblate, while that for Er III is prolate.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Therefore, the synthesis and characterization of high-nuclearity 3d-4f SMMs have attracted intensive attention in recent years. [5][6][7][8][9] Although many studies on 4f-4f or 3d-3d interactions have been reported, [10][11][12][13][14][15][16][17] research on 3d-4f exchange interactions is less developed. [18][19][20][21][22][23][24] Furthermore, according to the model of free-ion electron densities for all Ln III ions, the shape of the 4f electron density for the Dy III ion is oblate, while that for Er III is prolate.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the unique spectroscopic and magnetic properties, the lanthanides and their derivatives have numerous applications, including as NMR imaging agents [3,4], in optoelectronics applications [5], as luminescent materials (including probes in biology and medicine) [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], as new magnetic materials [20,21], as metal organic frameworks [22,23], as catalysts [24][25][26][27][28][29], and as vehicles for drug delivery in medicine [30,31]. Moreover, lanthanide species have been demonstrated be effective pharmaceuticals for the treatment of various diseases [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…13, 16,24,28 The complex contains Bi(III), a d 10 element, where ligand eld excited states are not possible. Charge transfer (CT) transitions in this complex may occur from a molecular orbital with a predominantly metal-like (M) character to another one with a ligand-like (L) character, exhibiting photoreactivity promoted by MLCT transitions.…”
Section: 26mentioning
confidence: 99%
“…The bond between the nitrogen and the metallic centre incorporates new functionalities into these types of molecules, such as photosensitivity. 14,16 A metal complex between Bi(III) and an alkanolamine, Nmethyldiethanolamine, is formed in solution and studied in this work. This complex presents primary bonds, Bi-O, Bi-N, and longer Bi-O-bonds, which can lead to the association of the monomer units.…”
mentioning
confidence: 99%
See 1 more Smart Citation